Peran Pemerintah Daerah dalam Pemenuhan Hak Atas Keadilan (Studi tentang Akses Bantuan Hukum bagi Masyarakat Miskin di Provinsi Jawa Timur) - Donny Michael (Jurnal HAM, 2012)
Ideally, if a person that is categorized as"the have" has a legal problem, she/he may appoint one or more lawyers to defend their interests. Likewise, someone who are poor (the have not) can also ask a defense from one or more public defender (public defenders) as workers in legal aid institute to defend their interests in a lawsuit. This condition must be fulfilled in order to implement the principle of equality before the law and equality of treatment and access to justice. In fact, a number of cases invite the public attention, which shows the lack of access to the poor to obtain legal assistance. This study aimed to describe the model of legal aid "probono" in the field, to identify and analyze the role of advocate, state or local government and law enforcement agencies in implementing the legal aid "probono", and to inventory and analyze supporting factors and obstacles in fulfilling legal aid for the poor. This research uses qualitative research, where the primary data collected from informants, obtained by in-depth interviews with informants including the legal agency of local government, law enforcement officers (police, prosecutors, judges), legal aid, academics from the universities, and people with legal problems. Secondary data collected from books, scholarly works, research reports, and documents related to the research topic.